2019
DOI: 10.1073/pnas.1815071116
|View full text |Cite
|
Sign up to set email alerts
|

OAS-RNase L innate immune pathway mediates the cytotoxicity of a DNA-demethylating drug

Abstract: Drugs that reverse epigenetic silencing, such as the DNA methyltransferase inhibitor (DNMTi) 5-azacytidine (AZA), have profound effects on transcription and tumor cell survival. AZA is an approved drug for myelodysplastic syndromes and acute myeloid leukemia, and is under investigation for different solid malignant tumors. AZA treatment generates self, double-stranded RNA (dsRNA), transcribed from hypomethylated repetitive elements. Self dsRNA accumulation in DNMTi-treated cells leads to type I IFN production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 52 publications
(93 reference statements)
2
52
1
Order By: Relevance
“…OAS1 is an antiviral protein (AVP) induced by interferon, and it plays an important role in antiviral immunity by regulating multiple signalling pathways 28,29 . Latest research showed that the OAS1 could regulate the antitumour activity and toxicity of AZA and related drugs by OAS‐RNase L innate immune pathway 30 . APOBEC3H is a member of the apolipoprotein B mRNA‐editing enzyme catalytic polypeptide 3 families of proteins, and it induces somatic mutagenesis in cancer cells that drive tumour evolution and may manifest clinically as recurrence, metastasis and/or therapy resistance 31 .…”
Section: Discussionmentioning
confidence: 99%
“…OAS1 is an antiviral protein (AVP) induced by interferon, and it plays an important role in antiviral immunity by regulating multiple signalling pathways 28,29 . Latest research showed that the OAS1 could regulate the antitumour activity and toxicity of AZA and related drugs by OAS‐RNase L innate immune pathway 30 . APOBEC3H is a member of the apolipoprotein B mRNA‐editing enzyme catalytic polypeptide 3 families of proteins, and it induces somatic mutagenesis in cancer cells that drive tumour evolution and may manifest clinically as recurrence, metastasis and/or therapy resistance 31 .…”
Section: Discussionmentioning
confidence: 99%
“…RNase L is a latent cytoplasmic exoribonuclease that is activated by 2′-5′ oligoadenylates produced by OASs 115 . Although OASs are highly interferon inducible, they are also expressed at a basal level and hence induce basal RNase L activity 116 . Importantly, this activity has been suggested to contribute to basal restriction of coronaviruses in myeloid cells, and hence to protect other cell types from infection 117 .…”
Section: Nucleases the Cytoplasm Contains Rnases Andmentioning
confidence: 99%
“…For example, OAS1 SNPs have also been implicated in altered cellular function leading to diseases including diabetes ( 37 ), multiple sclerosis ( 38 , 39 ), prostate cancers ( 40 ), and Sjögren's syndrome ( 41 , 42 ), as well as susceptibility to tuberculosis infection ( 43 ). OAS1 has also been recently implicated in cancer cell survival after treatment with DNA damaging agents ( 44 ) and in mediating the cytotoxicity of 5-azacytidine (AZA), a DNA methyltransferase inhibitor widely used in cancer treatment ( 45 ). Taken together, these studies suggest important roles for OAS1 in both innate immunity and other cellular processes that we have yet to fully elucidate.…”
Section: Introductionmentioning
confidence: 99%